2018
DOI: 10.1038/s41419-018-0753-0
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of dental pulp stem cell transplantation on a rat model of radioactivity-induced esophageal injury

Abstract: Dental pulp stem cell (DPSC) transplantation has been demonstrated to promote the regeneration and repair of tissues and organs and is a potentially effective treatment for radioactive esophageal injury. In this study, to explore the therapeutic effects of DPSCs on acute radiation-induced esophageal injury, DPSCs were cultured and transplanted into rats with acute radioactive esophageal injuries induced by radioactive 125I seeds in vivo. In the injured esophagus, PKH26-labeled DPSCs co-localized with PCNA, CK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The animal experiment showed the possibility of human DPSC can decrease the RGF loss in glaucoma which elevated intraocular pressure [ 51 ]. It is even reported to treat radioactive esophageal injury by regenerating esophageal tissues [ 87 ].…”
Section: Application Of Dpscs and Tissue Engineering Applicationsmentioning
confidence: 99%
“…The animal experiment showed the possibility of human DPSC can decrease the RGF loss in glaucoma which elevated intraocular pressure [ 51 ]. It is even reported to treat radioactive esophageal injury by regenerating esophageal tissues [ 87 ].…”
Section: Application Of Dpscs and Tissue Engineering Applicationsmentioning
confidence: 99%
“…Dental pulp stem cells (DPSCs), a type of MSC, are characterized by self-renewal, multipotent differentiation potential and amplification in vitro. Under appropriate extracellular stimuli, DPSCs differentiate into various lineages, including osteoblasts, neurons, vascular cells and hepatocytes [ 14 , 15 ]. Numerous studies have revealed that DPSCs could migrate to the lesion site, which accelerates tissue repair and regeneration [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The isolation of MSCs from dental tissues is convenient during the procedures. Hence, they are considered to be potent candidates for bone tissue engineering 5,6 .…”
Section: Introductionmentioning
confidence: 99%